Outcomes of meningococcal serogroup B disease: findings from a nationally representative case-control study. (29th September 2015) - Viner, RM; Latham, S; Hudson, L; Booy, R; Rajput, K; Bedford, H; Edmund, J; Kaczmarski, E; Christie, D
Abstract : Aims: There remain over 1000 cases of meningococcal serogroup B (MenB) disease in the UK each year. Vaccines to prevent other causes of meningitis and septicaemia have been successfully introduced into many countries. Estimates of the sequelae of MenB disease in the modern era are needed to inform the development and introduction of future vaccines. Methods: The authors present interim results from a nationally representative case-control study from five English regions. Cases were identified via the Meningococcal Reference Laboratory and controls via case general practitioners. Consenting subjects underwent a 2.5-h standardised assessment of hearing (audiometry), IQ and other cognitive function, psychological function and quality of life. Analyses were undertaken adjusted for age and sex. The study received ethics approval and was funded by the Meningitis Trust. Results: Data were available for 153 cases and 100 controls. Compared with controls, MenB survivors had lower verbal IQ (case mean 99, control mean 104; p=0.02), performance IQ (98 vs 102; p=0.04), were more likely to have any mental health disorder (24% vs 11%; p=0.04) and had poorer memory (p=0.008). Three survivors (2%) had cochlear implants compared with no controls. However, there were no significant differences between survivors and controls in proportions with mild or moderate hearing loss. Survivors were also more likely to receive Disability Living Allowance (9% vs 1%; p=0.009) and additional educational support (19% vs 6%; p=0.01). Conclusions: These interim results suggest MenB disease is associated with a significant burden of sequelae in survivors. These data will form the basis for cost-effectiveness analyses of new MenB vaccines.